Análise da ação da fotobioestimulação no reparo de feridas cutâneas induzidas em ratos desnutridos - Amadio, Eliane Martins (2019)
Photobiomodulation therapy (PBMT) has been indicated for wound healing through increased mitotic activity, number of fibroblasts, collagen synthesis and neovascularization; however, in unfavorable conditions such as protein malnutrition, photobiomodulation has not yet been fully studied. In view of the above, this study aimed to verify the effects of PBMT on healing in the proliferation phase in rats submitted to a hypoproteic diet. For this purpose 40 male rats (12 weeks) were used, of which 20 were normoproteic (25%) and 20 were submitted to 8% hypoproteic diet. The animals were divided into four experimental groups (n = 10) and submitted to cutaneous wound by means of 8 mm punch and treated by low intensity laser photobiomodulation (660 nm, 50 mW, 1.07 W / cm2, 0.028 cm2, 72 J / cm2, 2 J). The following analyzes were performed at the 7 and 14 days of the tissue repair process: semi-quantitative histopathological analysis (H&E), differentiation of the type I and III collagen I percentage by polarization of histological laminae stained with picrosirus red and labeling by immunohistochemistry of MMP- 3, MMP- 9 fibronectin and VEGF and test of mechanical resistance in machine universal test. . The results showed that there were significant differences between the normoproteic groups with lesion and their respective groups treated p <0.05, as well as for the treated and untreated hypoproteic groups p <0.001 in the semi-quantitative histopathological analysis and immunohistochemistry for the metalloproteinases 3 and 9 demonstrated that PBMT was able to decrease the immunostaining marking with statistical difference of p <0.01. There was also a decrease in the collagen deposition process with a statistical difference of p <0.05 for both types III collagen and I. We can conclude that low intensity laser photobiomodulation was effective in the treatment of cutaneous wounds in animals submitted to a hypoproteic diet, at different stages of the tissue repair process, but these alterations were more marked in the proliferation phase with increased formation of blood vessels and granulation tissue, as well as decreased metalloproteinases, providing better mechanical resistance of the injured area in the remodeling phase with type I collagen intest.